Space Utilization Policy in Payakumbuh City to Support The Public Transportation - Rahendra, Muhazir; Yossyafra, Yossyafra; Adji, Bayu Martanto (Universitas Negeri Padang, 2023)
The strategy that might be applied to increase the use of public transportation is to apply space utilization incentives and disincentives. Incentives and disincentives for space use contain elements of regulation and control that are accommodating to various actual changes that occur in cities. The stages of this research are: : 1) distribution of questionnaires, 2) ranking of Alternative Incentives and Disincentives with Likert scale. The formulation of incentives and disincentives for space utilization that are predicted to increase the use of public transportation, Alternative incentives sequentially are: 1) Policy for subsidizing public transportation fares, 2) Policy for Rejuvenating Public Transport Fleet, 3) Improving infrastructure and supporting facilities for the use of public transportation, and for Disincentives: 1) Progressive Tax Implementation Policy on vehicle ownership, 2) Mandatory garage policy for prospective owners of private vehicles. The results of this study can be used as input for the Payakumbuh City government in making decisions related to spatial planning and transportation and further research needs to be done on alternative incentives and disincentives that have been formulated.